2013
DOI: 10.1227/01.neu.0000431477.02408.5e
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Prognostic Factors of Anaplastic Gliomas

Abstract: First-course radiation, younger age, female sex, treatment in recent years, and surgery were associated with improved survival in AA patients. In contrast, age was the most prominent predictor of survival in AO patients. Surgery alone did not seem to benefit AO patients, and gross total resection improved survival by 21 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 39 publications
3
30
2
1
Order By: Relevance
“…The median OS and RFS of the histological subgroups and the AGs as a group in our study is consistent with published literature;5 25 32 38 however, some studies have shown better prognosis in AOs 3 6 32 37 39. Analysis of biomarker expression expectedly revealed p53 positivity and ATRX loss to be associated with AAs (p<0.001) and 1p/19q codeletion to be associated with AOs (p<0.001), whereas IDH1- R132H positivity and m MGMT did not show significant association with the histological subgroups of AG, which is consistent with the current understanding that IDH1- R132H mutations are believed to constitute one of the earliest step in tumorigenesis followed by either p53 mutations/ ATRX loss or 1p/19q codeletion which are believed to drive differentiation towards an AA or AO phenotype, respectively, with MGMT promoter methylation being an epigenetic event 15 16 20 21 25 40–42…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The median OS and RFS of the histological subgroups and the AGs as a group in our study is consistent with published literature;5 25 32 38 however, some studies have shown better prognosis in AOs 3 6 32 37 39. Analysis of biomarker expression expectedly revealed p53 positivity and ATRX loss to be associated with AAs (p<0.001) and 1p/19q codeletion to be associated with AOs (p<0.001), whereas IDH1- R132H positivity and m MGMT did not show significant association with the histological subgroups of AG, which is consistent with the current understanding that IDH1- R132H mutations are believed to constitute one of the earliest step in tumorigenesis followed by either p53 mutations/ ATRX loss or 1p/19q codeletion which are believed to drive differentiation towards an AA or AO phenotype, respectively, with MGMT promoter methylation being an epigenetic event 15 16 20 21 25 40–42…”
Section: Discussionsupporting
confidence: 92%
“…Among the other clinical variables analysed, the factors that were predictive of OS and RFS were GTR and administration of radiochemotherapy. Compared with STR, patients who underwent GTR had significantly prolonged OS and RFS, translating into 26 and 27 months increase in median OS and RFS time, respectively, which is consistent with published literature 5 32 37. In our cohort, all patients had received radiotherapy and 42% received additional chemotherapy (radiochemotherapy), which resulted in prolonged OS and RFS, an 18.1 months increase in mean OS and 28.5 months increase in median RFS when compared with those treated with radiotherapy alone.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…More recently, a total of 1,766 patients with AA were studied using the SEER registry, describing additional factors associated with the hazard of mortality in AA patients, such as type of surgery and marriage status [16]. From molecular genetics predictors, IDH1 mutation is most strongly associated with improved survival [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, the latter group shows a broad survival variant [1][2][3]. Survival of anaplastic gliomas has been related to age, Karnofsky Performance Status (KPS), extent of surgical resection, treatment modalities, and sensitivity to chemotherapy as determined by genetic mutations such as isocitrate dehydrogenase 1 gene (IDH1), phosphatase and tensin homolog, epidermal growth factor receptor amplification, and 1p19q co-deletion [1,2,[4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%